Orientalism in Outer-space: The Ascendancy of Sanskrit Mantras in Hollywood Science Fiction Films and Soundtracks - Dunbar, Scott Daniel (Journal for the academic study of religion, 2008)
Several Hollywood science fiction films have recently appropriated Sanskrit mantras as a prominent feature in their musical soundtracks. Notably, Hollywood’s use of ‘SF Sanskrit’ tends to evoke a sense of militancy and war rather than tranquillity and peace, which has resounding Orientalist connotations. Nevertheless, it will be shown that the correlation between mantras and warfare actually has historical precursors within the Hindu tradition. To advance this thesis, two case studies are examined: (1) The Matrix Revolutions and (2) Star Wars Episode I—The Phantom Menace. It will be shown that each of these films presents mantras in cinematic contexts evoking militancy and war. Such positioning of Sanskrit in belligerent film space, however, raises interesting questions about evolving Orientalist stereotypes in popular culture: Why is Sanskrit associated with war in the SF industry? Is Hollywood’s appropriation of Hindu mantras a new ‘fad’ to market SF in ‘exotic’ Indian packaging or an effort to ‘spiritualise’ the genre? What does Hollywood’s use of Sanskrit tell us about emerging views of Hinduism in modern SF films, and about shifting views of the ‘Orient’ in popular culture?